Validation of a UV-VIS Spectrophotometric method for the determination of usnic acid /collagen-based membranes - Nunes, Paula Santos; Jesus, Douglas Costa; Bezerra, Marília Santos; Souza, Jamille Cristina Campos; Silva, Francilene Amaral; Serafini, Mairim Russo; Lima, Bruno Santos; Shanmugam, Saravanan; Albuquerque Junior, Ricardo Luiz Cavalcanti; Araújo, Adriano Antunes de Souza (Scientia Plena, 2015)
The usnic acid (UA) is a secondary metabolite of lichen that has shown potential pharmacological effects such as antimicrobial, antiviral, antiproliferative and anti-inflammatory activities. Collagen is one of the most useful biomaterials with various applications as drug delivery systems. The aim of this study was to develop and validate a quantitative UV spectrophotometric method for the determination of UA levels in collagen membranes. The validation parameters were assessed according to the Brazilian Health Surveillance Agency (ANVISA). The specificity revealed that the excipients in the formulation did not interfere with the analysis. The linearity in the range of 2-10 μg/mL presented a correlation coefficient of 0.9994. The method showed excellent repeatability (Relative Standard Deviation (RSD) < 1.0%). The accuracy revealed a mean percentage recovery of 100.43%. The method was robust for the variation of temperature and solvent. The detection and quantization limits were found at 0.109 and 0.364 µg/mL. The total rate recovery from the analyzed membranes showed values between 100.4 and 83.2%.